Annual forum of lawyers in the capital of oil of Kazakhstan – the city of Atyrau (Journal of actual problems of jurisprudence, 2019)
In this article the author writes about an anniversary conference at which they discussed topical issues related to the management ofmineral resources, the problem of stability of legislation and the formation of law enforcement.